IDENTITY CRISIS BASED ON REALITY AND FANTASY IN “THE JUNGLE BOOK” BY RUDYARD KIPLING - Dea Noor Amelia; Gustaman Saragih (Universitas Indraprasta PGRI, 2022)
The aim of this study is to analyze how the plot of the story represents an identity crisis issue and the character’s action in dealing with his problems to manage his identity crisis. The reality and fantasy of the main character portrays the character’s identity crisis influencing his personality. The study employed qualitative method with the descriptive analysis. In identifying the data, Erikson’s theory about identity crisis and the interpretation of dreams by Sigmund Freud are used to find out the main character’s Id and how he manages his Id. The results of this study show the main character’s Id in The Jungle Book can be seen through the reflection of his anxiety through Freud theory. His anxiety and identity crisis have a significant role in Mowgli’s thoughts and behaviors: he cannot define himself in one’s identity. It comes to the conclusion that he is not a man, but neither a wolf.